(untitled) - Bruice, Paula Yurkanis (Englewood Cliffs, New Jersey, 1998)
An innovative text which takes a mechanistic approach to organic chemistry. The book emphasizes the commonalities of chemical reactors as a means of fostering comprehension rather than rote memorization of functional groups. The text covers both traditional topics and bio-organic chemistry.
Keywords: chemistry, organic